Agriculture for Improved Nutrition: Seizing the Momentum 2019
DOI: 10.1079/9781786399311.0027
|View full text |Cite
|
Sign up to set email alerts
|

Food value chains for nutrition.

Abstract: This chapter focuses on understanding the supply and demand aspects of food value chains and their relationship to nutrition using a food-systems perspective. It considers the collaborative roles of value chain actors, including producers, consumers, organizations, businesses, and the public sector. Finally, the chapter provides specific examples of interventions that have strived to put food value chains to work for nutrition and the lessons learned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
5
0
2
Order By: Relevance
“…To efficiently assess how the highly dynamic food systems can best contribute to leverage nutrition equitably and deal with trade-offs, a systems approach is needed (Gillespie et al, 2019). A strategic mechanism to address the nutritious food access gap is the promotion of inclusive agri-food value chains for nutrition (i.e., profitable for everyone involved, and linked to equitable markets) (Allen et al, 2019). These identify entry points for interventions targeting the supply and demand of nutritious foods, as well as approaches and policies to increase the smallholders income, reduce loss and waste or promote an enabling environment for nutrition (FAO, 2016).…”
Section: Food Systems and Malnutrition Food System-related Malnutrition And Potential Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…To efficiently assess how the highly dynamic food systems can best contribute to leverage nutrition equitably and deal with trade-offs, a systems approach is needed (Gillespie et al, 2019). A strategic mechanism to address the nutritious food access gap is the promotion of inclusive agri-food value chains for nutrition (i.e., profitable for everyone involved, and linked to equitable markets) (Allen et al, 2019). These identify entry points for interventions targeting the supply and demand of nutritious foods, as well as approaches and policies to increase the smallholders income, reduce loss and waste or promote an enabling environment for nutrition (FAO, 2016).…”
Section: Food Systems and Malnutrition Food System-related Malnutrition And Potential Responsesmentioning
confidence: 99%
“…In lowand middle-income settings, specific challenges exists related to high costs of distribution, inadequate infrastructure, food quality requirements, lack of foods safety regulations, rapid transformation of the food systems (from traditional and informal, to modern production and retail outlets) and of the preferences and demand. These are not well understoodincluding their role in nutrition (Allen et al, 2019). For example, a recent study in Kenya suggested that the spread of supermarkets in emerging economies could be influencing dietary habits and contributing to rising population numbers of overweight people and obesity (Demmler et al, 2017;Qaim, 2019).…”
Section: Food Systems and Malnutrition Food System-related Malnutrition And Potential Responsesmentioning
confidence: 99%
“…Food VC approaches have been mainly used to improve the livelihoods of food producers, streamline the supply chain, and maximize profits, 12 and in rural development to enhance commercial relations for economic benefits. 13 Value chain analysis (VCA) has been used to investigate food production, nutrition, and food safety in the dairy VC in Tanzania, 14 reduce micronutrient deficiencies while creating livelihood opportunities for VC actors through the introduction of fortified rice in Myanmar, 15 assess the potential of the private sector manufacturers of fortified foods to reach poor households, 16 and evaluate the status of flour fortification in Kenya on the adoption of mandatory fortification practices by millers. 17 Thus, in the nutritional context, VCA is used as a diagnostic tool for food-based VCs to identify barriers (and potential solutions) to improved availability, accessibility, affordability, and acceptability of micronutrient-dense foods.…”
Section: Introductionmentioning
confidence: 99%
“…The private sector also needs incentives to promote nutrition goals; this can be achieved by creating market demand for nutritious foods, such as through information and education campaigns, or by adding “visible value” through nutrition labeling. (Allen et al , 2019). Public policy, in the form of regulation, can also advocate for consumer health and nutrition.…”
Section: Introductionmentioning
confidence: 99%